La enseñanza de la bioética y su relación con la enseñanza de la clínica. Experiencia de la Escuela de Medicina de la Universidad de Chile - Valenzuela P., Sergio (Revista Hospital Clínico Universidad de Chile, 2009)
This article is intended to describe to clinicians what the Department of Education in Health Sciences means to pre graduation teaching of bioethics, through its historical development, its educational objectives and its contents. There is yet no consensus among different Schools about the methods used to teach the discipline and its purpose, so discussion provokes reflection and alternative decisions. The concept and significance of the “hidden curriculum”, derived from the afore explicit terminology with polisemic interpretation, adds to the debate as it produces new entrances to the pool of meanings, varying from knowledge and cultureincrements to deliberated and malicious imposition of information. It seems mandatory to all the clinical tutors to assume direct responsibility in students ethics problems analysis, as part of their general competences and reflecting the usual clinical exposure to these situations and the importance that knowing to handle these events has in the medical setting.